Relevansi pancasila sebagai dasar negara dan paradigma kehidupan dalam menghadapi tantangan globalisasi dan dinamika sosial di indonesia - Maulana, Muhammad Machreza (Maliki Interdisciplinary Journal, 2025)
Pancasila is the foundation of the state and the philosophy of the Indonesian people, which plays a crucial role in maintaining the direction and identity of the Indonesian nation. Facing complex global trends, implementing Pancasila in daily life is one way to safeguard the sovereignty of the Indonesian nation. Pancasila is both the foundation of the state and the nation's philosophy. Pancasila can safeguard and foster the identity of the Indonesian nation in the face of globalization. Indonesia has become independent, and Pancasila serves as a guideline for implementing its core values ​​in addressing every challenge. In social issues, as long as Pancasila serves as a guideline, the nation will have a positive identity. Pancasila and its values ​​serve to build strong unity, a spirit of preserving sovereignty and culture, and the sovereignty of the Indonesian nation amidst globalization and the currents of world cultural modernization. Thus, Pancasila, as the soul and foundation of the state, serves as a guarantee for maintaining the nation's sovereignty and socio-cultural unity.